O papel do judiciário frente ao direito à moradia no município de Olinda - Duarte, Alvaro Henrique de Araujo (2013)
This thesis aims to study the mechanisms of justification in judicial decisions concerning the right to housing in the city of Olinda aims to answer whether there is violation of the fundamental right to housing and discuss their effectiveness with the legal system. It is, therefore, a jurisprudential literature search conducted in the 1stand 2nd of Public Finance Courts in Olinda Court of Pernambuco. The study analyzed the legislation concerning the right to housing and the decisions of Repossession actions involving public for withdrawal of low-income families for project deployment of PAC-Urbanization Plan for Accelerated Growth. Although there are a countless number of provisions that guarantee the property as a fundamental right of human beings (caput of Article 6 of the Federal Constitution 1988) its realization by judicial process is still tenuous, lacking density law with respect to constitutional provisions.